1965
DOI: 10.1002/polc.5070110115
|View full text |Cite
|
Sign up to set email alerts
|

The sorption of glucomannan and xylan on α‐cellulose wood fibers

Abstract: The rates of sorption of spruce glucomannan and of a modified birch xylan (containing less than 3% uronic anhydride) upon never‐dried α‐cellulose wood fibers in 0.02N alkali have been measured at 4 temperatures ranging from 5–40°C. By labeling the glucomannan with carbon‐14 and the xylan with tritium it was possible to measure the rates of sorption of each hemicellulose alone or in solution together at the same concentration. In both cases the rates of sorption of the glucomannan were about twice those for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
(1 reference statement)
0
14
0
Order By: Relevance
“…The sorption of gluco-further improved and the kappa number was reduced mannan on cellulose has been found to proceed faster to 15.4 or 14.7, respectively, and the brightness was inand also to a greater extent than the sorption of xylan creased from 43.1% to 44.9 and 45.4, respectively. (Clayton and Phelps 1965). Thus the sorption of xylan Previously, it has been observed that Bacillus subtilis probably takes place on wood fibres already contain-mannanase had only a slight effect on the bleachabiing the sorbed glucomannan (Hansson and Hartler lity of pine kraft pulp in peroxide delignification (Kan-1969).…”
Section: Hydrolysis Of Softwood Kraft Pulp With T Reesei Xylanase Anmentioning
confidence: 95%
“…The sorption of gluco-further improved and the kappa number was reduced mannan on cellulose has been found to proceed faster to 15.4 or 14.7, respectively, and the brightness was inand also to a greater extent than the sorption of xylan creased from 43.1% to 44.9 and 45.4, respectively. (Clayton and Phelps 1965). Thus the sorption of xylan Previously, it has been observed that Bacillus subtilis probably takes place on wood fibres already contain-mannanase had only a slight effect on the bleachabiing the sorbed glucomannan (Hansson and Hartler lity of pine kraft pulp in peroxide delignification (Kan-1969).…”
Section: Hydrolysis Of Softwood Kraft Pulp With T Reesei Xylanase Anmentioning
confidence: 95%
“…The difficulty to remove the adsorbed xylans even by 10-20% NaOH (Hansson 1970) suggests that the sorption is not limited at the outer fibre surfaces. Similarly Clayton and Phelps (1965) brought evidence of the involvement of internal surfaces in the retention of xylans. More recently in a study about the rates of alkaline extraction of hemicelluloses from pulp fibres, Scott (1984) came to the conclusion that the extraction is highly dependent on the hemicelluloses distribution, near outer fibre surfaces and on, or near, the lumen surfaces and pores.…”
Section: Introductionmentioning
confidence: 97%
“…The model experiments carried out have shown that the both during pulping (Yllner and Enström 1956; Yllner and sorption of a hemicellulose molecule on a cellulose fibre is Enström 1957; Clayton and Stone 1963) and as model affected by the initial concentration of the polysaccharide in the experiments (Most 1957;Croon and Enström 1961;Hart-solution (Yllner and Enström 1956;Most 1957;Russo Ier and Lund 1962;Clayton and Phelps 1965;Marches-and Thode 1960), the ratio of solid to liquor (Most 1957), sault, Settineri and Winter 1967; Hansson and Hartler the P H of the solution (Most 1957;Clayton and Stone 1963;, but some research has also been done with glucomannan Aurell 1965), the intensity of mixing (Russo and Thode (Most 1957;Clayton and Phelps 1965;Laffend and 1960), die temperature (Most 1957;Russo and Thode 1960;Swenson 1968). Hartler and Lund 1962;Clayton and Phelps 1965), the time (Yllner and Enström 1956;Most 1957 l er and Lund 1962) and the nature of the cellulose fibre (Yllner and Enström 1956;Croon and Enström 1961;Axelsson, Croon and Enström 1962).…”
Section: Introductionmentioning
confidence: 99%